Community Service as an Instrument for Enhancing Social Capacity: A Social Capital and Community Resilience Perspective - Ahmad Yani; Sonny Santosa (PT. LITERASI SAINS NUSANTARA, 2026)
This study aims to examine community service as an instrument for enhancing community social capacity through the perspectives of social capital and community resilience. The study employs a literature review method with a qualitative approach and descriptive analysis, focusing on expanding and enriching scholarly references related to community service. Data were obtained from Google Scholar and selected credible websites, covering publications from 1994 to 2026. Of the 50 articles identified at the initial stage, a rigorous selection process based on topic relevance, methodological quality, and source credibility resulted in 30 articles being analyzed in depth. The findings indicate that community service programs designed in a participatory and contextual manner play a significant role in strengthening social capital, enhancing collective capacity, and building community resilience. The integration of social capital and community resilience perspectives effectively explains the mechanisms through which community service contributes to sustainable social development. This study emphasizes the importance of community service as a strategic component of community-based development and provides a conceptual contribution to the advancement of community service studies and practices in the future.